2010
DOI: 10.1161/circheartfailure.109.862359
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Alcohol Septal Ablation in Patients With Obstructive Hypertrophic Cardiomyopathy

Abstract: Background-The impact of alcohol septal ablation (ASA)-induced scar is not known. This study sought to examine the long-term outcome of ASA among patients with obstructive hypertrophic cardiomyopathy. Methods and Results-Ninety-one consecutive patients (aged 54Ϯ15 years) with obstructive hypertrophic cardiomyopathy underwent ASA. Primary study end point was a composite of cardiac death and aborted sudden cardiac death including appropriate cardioverter-defibrillator discharges for fast ventricular tachycardia/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(88 citation statements)
references
References 40 publications
3
78
1
4
Order By: Relevance
“…The relatively better survival of the ASA group in this study vs. several previous reports may be explained by the fact that patients in the ASA group of our study were younger (mean age: 49.8 years) than those from the other studies (mean age: 54-64 years) [8,[25][26][27]. There were reports demonstrating the survival advantage of patients younger than 60 years or 65 years [25,28].…”
Section: Discussioncontrasting
confidence: 59%
“…The relatively better survival of the ASA group in this study vs. several previous reports may be explained by the fact that patients in the ASA group of our study were younger (mean age: 49.8 years) than those from the other studies (mean age: 54-64 years) [8,[25][26][27]. There were reports demonstrating the survival advantage of patients younger than 60 years or 65 years [25,28].…”
Section: Discussioncontrasting
confidence: 59%
“…This may be important since higher outflow gradients after ASA are associated with a less favourable long-term haemodynamic outcome [6]. Additionally, even though metaanalyses have shown comparable long-term outcome between ASA and myectomy, in a recently published single-centre study, a higher rate of aborted sudden cardiac death was found after ASA compared with myectomy and therefore myectomy was advised as the preferred treatment [3].…”
Section: Discussionmentioning
confidence: 99%
“…However, gradient reduction after ASA was slightly less favourable [1,2] and in a singlecentre study a higher rate of aborted sudden cardiac death was found [3]. The following case report illustrates the importance of coronary anatomy and infarction location in determining the outcome after ASA.…”
Section: Introductionmentioning
confidence: 92%
“…Such fears were heightened by some small observational studies, 32,33 but these were contradicted by other similar studies that indicated the technique was safe. 34,35 These conflicting results, and the lack of sufficient evidence, have created confusion that can only be resolved by large studies of patients treated by ASA with long-term outcomes and by meta-analyses comparing the results of the two techniques.…”
Section: Comparison With Myectomymentioning
confidence: 99%